Instilling democratic values in social science learning in junior high school - Wati, Mila; Saleh, Syarbaini (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The importance of instilling democratic values in education cannot be ignored given the increasingly complex global challenges, such as political polarization, social conflicts, and injustice. Through social studies learning, students are not only taught about democratic theories, but also given the opportunity to practice participating in the democratic process, such as through election simulations or group discussions on social issues. Thus, the purpose of this study is to explore how democratic values can be integrated in social studies learning in grade VIII, as well as to evaluate the effectiveness of the approaches applied in the context of democracy education. The method used in this study is to use a descriptive qualitative research approach with informants from social science teachers, grade VIII students, principals, deputy principals and one of the homeroom teachers of grade VIII. The results of this study suggest that 1) Implementation of Group Discussion: in this case the teacher emphasizes the importance of group work to foster a sense of responsibility among students; 2) Educators use a variety of strategies to instill democratic values, including facilitating discussions that encourage students to express their opinions freely; 3) This involvement is related to their ability to practice democratic values, such as tolerance and respect for different viewpoints; 4) a supportive school environment, including the involvement of teachers and school leaders, plays an important role in the successful implementation of democratic values in the curriculum; 5) The effectiveness of the teaching used in integrating democratic values into the learning process; 6) Supporting and inhibiting factors: a) supporters, namely educators, students, facilities or infrastructure, and school culture; b) Obstacles are limited time and lack of motivation for students' learning.